Pentaho 8 Reporting for Java Developers - Corti, Francesco (Packt Publishing Limited, 2017)
bCreate reports and solve common report problems with minimal fuss./bh2About This Book/h2ulliUse this unique book to master the basics and advanced features of Pentaho 8 Reporting./liliA book showing developers and analysts with IT skills how to create and use the best possible reports using the Pentaho platform./liliWritten with a very practical approach: full of tutorials and practical examples (source code included)./li/ulh2Who This Book Is For/h2This book is written for two types of professionals and students: Information Technologists with a basic knowledge of Databases and Java Developers with medium seniority.
Keywords: COMPUTERS / Data Modeling & Design; COMPUTERS / Data Visualization